Molecular genetic analysis of human immunodeficiency virus antiretroviral therapy response in South Africa : a pharmacogenetics study - Parathyras, John Burns (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Genetics))--University of Stellenbosch, 2007.